Synthesis, Characterization, X-Ray Crystallography, and Antileishmanial Activities of N-Linked and O-Linked Glycopyranosides - Haroon ur Rashid; Sher Wali Khan; Momin Khan; Akhtar Nadhman; Noor Rehman; Muhammad Tariq; Sammer Yousuf (Journal of Chemistry)
Novel N-linked 5a–e and O-linked glycopyranosides 7a–e were synthesized in high yield from commercially available L-tartaric acid containing two asymmetric centers and C2 axis of symmetry. The compound L-tartaric acid was completely protected and then partially hydrolyzed to get the monoester, which upon treatment with different amino and hydroxyl derivatives of glycopyranoses gave the desired amides and esters. The synthesized derivatives were purified by chromatography and characterized by spectroanalytical techniques. The structure of compound 7c in the series was supported by X-ray analysis. Leishmanicidal activities of compounds 5a–e and 7a–e were investigated which showed moderate to good activities.